A wavelength-convertible quantum memory: Controlled echo - Byoung S. Ham (Nature Portfolio, 2018)
Abstract Quantum coherence control is reinvestigated for a new physical insight in quantum nonlinear optics and applied for a wavelength-convertible quantum memory in a solid ensemble whose spin states are inhomogeneously broadened. Unlike typical atomic media whose spin decays are homogeneous, a spin inhomogeneously broadened solid ensemble requires a counter-intuitive quantum coherence control to avoid spontaneous emission-caused quantum noises. Such a quantum coherence control in a solid ensemble satisfying both near perfect retrieval efficiency and ultralong photon storage offers a solid framework to quantum repeaters, scalable qubit generations, quantum cryptography, and highly sensitive magnetometry. Here, the basic physics of the counter-intuitive quantum coherence control is presented not only for a fundamental understanding of collective ensemble phase control but also for a coherence conversion mechanism between optical and spin states involving Raman rephasing.